An overview of the new routing algorithm for the ARPANET. - McQuillan, John M. (Computer communication review.)
The original routing algorithm of the ARPANET, in service for over a decade, has recently been removed from the ARPANET and replaced with a new and different algorithm. Although the new algorithm, like the old, is a distributed, adaptive routing algorithm, it is not similar to the old in any other important respect. In the new algorithm, each node maintains a data base describing the delay on each network line. A shortest-path computation is run in each node which explicitly computes the minimum-delay paths (based on the delay entries in the data base) from that node to all other nodes in the network. The average delay on each network line is measured periodically by the nodes attached to the lines. These measured delays are broadcast to all network nodes, so that all nodes use the same data base for performing their shortest-path computations. The new routing algorithm was extensively tested on the ARPANET before being released. This paper describes the algorithm and summarizes the results of these tests.